The "evolutionary field" hypothesis. Non-Mendelian transgenerational inheritance mediates diversification and evolution. (May 2018) - Spadafora, Corrado
Abstract: Epigenetics is increasingly regarded as a potential contributing factor to evolution. Building on apparently unrelated results, here I propose that RNA-containing nanovesicles, predominantly small regulatory RNAs, are released from somatic tissues in the bloodstream, cross the Weismann barrier, reach the epididymis, and are eventually taken up by spermatozoa; henceforth the information is delivered to oocytes at fertilization. In the model, a LINE-1-encoded reverse transcriptase activity, present in spermatozoa and early embryos, plays a key role in amplifying and propagating these RNAs as extrachromosomal structures. It may be conceived that, over generations, the cumulative effects of sperm-delivered RNAs would cross a critical threshold and overcome the buffering capacity of embryos. As a whole, the process can promote the generation of an information-containing platform that drives the reshaping of the embryonic epigenetic landscape with the potential to generate ontogenic changes and redirect the evolutionary trajectory. Over time, evolutionary significant, stably acquired variations could be generated through the process. The interplay between these elements defines the concept of "evolutionary field", a self-consistent, comprehensive information-containing platform and a source of discontinuous evolutionary novelty.